Scenario Planning of the Future of Strategic Agility in the Ministry of Sports and Youth of the Islamic Republic of Iran - Mojgan Ghalenoei; Lora Chapari; Zahra Hojabrnia; Zahra Alam (Shahid Bahonar University of Kerman, 2023)
The present study was conducted with the aim of scenario planning of the future of strategic agility in the Ministry of Sports and Youth of the Islamic Republic of Iran through using future research. The method used in this research is scenario-based planning, which is designed and performed in eight steps. The method of data collection in this qualitative study was based on interview, expert panel and Delphi survey. Twenty experts with specialized knowledge or practical experience were selected as the participants of the research through using snowball sampling. In the first part, acceleration to affairs and processes, the application of new managerial competencies, innovative and agile organizational structure, the use of emerging technologies, and the existence of a system of encouragement and punishment based on strategic agility were identified as key drivers. In the second part, it identifies and describes possible and compatible scenarios based on the drivers and related uncertainties, and it was found that out of the two proposed scenarios, only one scenario is in a promising situation. According to this scenario, by increasing the speed of the affairs and processes, the use of new managerial competencies, agile organizational structure, emerging technologies, and the existence of an incentive system, we can see the improvement of strategic agility in the Ministry of Sports and Youth.